2017
DOI: 10.1021/acs.jchemed.6b00988
|View full text |Cite
|
Sign up to set email alerts
|

Using Photocatalytic Oxidation and Analytic Techniques To Remediate Lab Wastewater Containing Methanol

Abstract: This experiment is dedicated to second-year and above undergraduates who are in their experimental session of the analytical chemistry course. Grouped students are required to use a TiO2 photocatalytic oxidation process to treat the methanol-containing wastewater that resulted from their previous HPLC experiments. Students learn to assemble a specified apparatus for a chemical reaction and analytical methods for the determination of environmental pollutants and reaction intermediates. The comprehensive experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…27,28 The existing proposals cover a wide range of possibilities: innovations based on scale models of water treatment plants; 29,30 laboratory experiments in which water quality is monitored; 31,32 the elimination of pollutants in wastewater, 33,34 including processes involving the use of adsorbing agents as carbons 35−37 or magnetic carbons; 38,39 the use of electrochemical methods to decontaminate water; 40−42 and the use of methods in which light serves as a key agent in the decontamination of wastewater. 43,44…”
Section: Didactic Innovations In Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The existing proposals cover a wide range of possibilities: innovations based on scale models of water treatment plants; 29,30 laboratory experiments in which water quality is monitored; 31,32 the elimination of pollutants in wastewater, 33,34 including processes involving the use of adsorbing agents as carbons 35−37 or magnetic carbons; 38,39 the use of electrochemical methods to decontaminate water; 40−42 and the use of methods in which light serves as a key agent in the decontamination of wastewater. 43,44…”
Section: Didactic Innovations In Wastewater Treatmentmentioning
confidence: 99%
“…The concern for sustainability has reached education at all levels from early childhood education to higher education. Regarding university studies, there is a wealth of literature on wastewater management. , The existing proposals cover a wide range of possibilities: innovations based on scale models of water treatment plants; , laboratory experiments in which water quality is monitored; , the elimination of pollutants in wastewater, , including processes involving the use of adsorbing agents as carbons or magnetic carbons; , the use of electrochemical methods to decontaminate water; and the use of methods in which light serves as a key agent in the decontamination of wastewater. , …”
Section: Introductionmentioning
confidence: 99%
“…The concept and study of photocatalysis have also received increasing emphasis in undergraduate chemistry courses recently. Many teaching experiments and reactors about heterogeneous photocatalytic degradation and oxidation of pollutants have been reported, which help students to understand the basic chemistry, concepts, and extensive applications of semiconductors and photocatalysis. For instance, Tatarko et al and Chen et al designed a cheap photocatalytic reactor and a simple parallel photochemical reactor for the remediation of the azo dye Congo Red and methylene blue in water for undergraduate students, respectively. , Boffa et al prepared sol–gel-derived TiO 2 powders for the photodegradation of toluidine blue in solution using UV–vis light, thus effectively introducing undergraduate students to materials chemistry . Pitcher et al described a simple demonstration of photocatalysis using the photodegradation of 2,6-dicholorophenolindophenol sodium salt (DCIP) over the commercially available TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Stefanov et al developed a relatively cheap and readily available 3D-printed gas-phase photocatalytic equipment for online monitoring of air-pollutant photodegradation, demonstrating the advanced scientific topics for chemical-engineering students . More recently, Xiong et al used a TiO 2 -photocatalytic-oxidation process to treat methanol-containing wastewater, from which students can understand the basic principle of photocatalytic oxidation reactions and learn to assemble a specified apparatus for a chemical reaction and analytical methods . Interestingly, Rimoldi et al demonstrated the application of irradiation-induced superhydrophilicity of TiO 2 films to achieve surface-wetting properties for Master’s students .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation